2010
DOI: 10.1093/bja/aeq232
|View full text |Cite
|
Sign up to set email alerts
|

High-volume local infiltration analgesia combined with intravenous or local ketorolac+morphine compared with epidural analgesia after total knee arthroplasty

Abstract: LIA with local adjuvants compared with epidural analgesia results in reduced opioid consumption, faster mobilization, and earlier readiness for hospital discharge. Ketorolac and morphine are more efficient when given locally than systemically. The study has been registered at clinicaltrials.gov (NCT00562627) before onset of participant enrolment: http://clinicaltrials.gov/ct2/show/NCT00562627?term=spreng&rank=2 (April 21, 2010).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
125
2
6

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(133 citation statements)
references
References 26 publications
0
125
2
6
Order By: Relevance
“…374 Twenty-three studies were in patients undergoing TKR. 380,381,386,[397][398][399][400][401][402][403][404][405][406][407][408][409][410][411][412][413][414] Small study effects Inspection of funnel plots for each meta-analysis gave no strong indication of publication bias or small study effects, but numbers of studies in individual analysis groups were small, such that assessment of asymmetry was difficult.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…374 Twenty-three studies were in patients undergoing TKR. 380,381,386,[397][398][399][400][401][402][403][404][405][406][407][408][409][410][411][412][413][414] Small study effects Inspection of funnel plots for each meta-analysis gave no strong indication of publication bias or small study effects, but numbers of studies in individual analysis groups were small, such that assessment of asymmetry was difficult.…”
Section: Resultsmentioning
confidence: 99%
“…The mean number of patients randomised was 63 (range 32-101). We assessed that 17 studies were at low risk of bias 386,[399][400][401][402][403][404][405][406][407][408][409][411][412][413] and that five studies had unclear risk of bias based on uncertainty about blinding of outcome assessments. 380,397,398,410,414 One study was assessed to be at high risk of bias owing to a large uneven loss to follow-up between randomised groups.…”
Section: Long-term Outcomesmentioning
confidence: 99%
“…The use of combined sciatic and femoral nerve blocks over femoral nerve block alone has been shown to have improved pain scores and seems more beneficial for pain management [1,10,17]. When comparing intraoperative periarticular injections with intraarticular injections given after closure of the capsule, better pain scores are generally found in studies using periarticular injections [12,15,30,36]. With the exception of a few studies showing minimal improved pain [24,32], the majority of studies using intraarticular injections showed no improvement in pain scores postoperatively [3,5,15,19,27].…”
Section: Discussionmentioning
confidence: 99%
“…From these we identified 12 eligible RCTs. [3][4][5][6][7][8][9][10][11][12][13][14] Inter-observer agreement for trial eligibility was good (kappa = 0.75; SE 0.053). Table I reports the characteristics of the included trials and the local anaesthetic protocols used in the trials.…”
Section: Trial Identification and Selectionmentioning
confidence: 95%